2010
DOI: 10.1159/000320923
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cytogenetics of Giant Trahiras <i>Hoplias aimara </i>and <i>H. intermedius </i>(Characiformes, Erythrinidae): Chromosomal Characteristics of Minor and Major Ribosomal DNA and Cross-Species Repetitive Centromeric Sequences Mapping Differ among Morphologically Identical Karyotypes

Abstract: Karyotype and cytogenetic characteristics of 2 species of giant trahiras, Hopliasintermedius, São Francisco river basin, and Hopliasaimara, Arinos river (Amazon basin), were examined by conventional (C-banding, Ag-NOR, DAPI/CMA3 double-staining) and fluorescent in situ hybridization (FISH) with 5S, 18S rDNA probes and cross-species Cot-1 DNA probing. Both species invariably had diploid chromosome number 2n = 50 and identical karyotypes composed of 10 pairs of metacentric and 15 pairs of submetacentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 65 publications
3
20
0
1
Order By: Relevance
“…The 2 species, H. intermedius and H . aimara, have identical 2n = 50 karyotypes, but 1 and 2 rDNA-bearing chromosome pairs, respectively [Blanco et al, 2011]. In contrast, in H. malabaricus (2n = 40/42), the number of NOR-bearing chromosomes ranges from 4 to 7 [Born and Bertollo, 2000;Cioffi et al, 2009].…”
Section: Interspecific and Intergeneric Variation In The Number And Lmentioning
confidence: 99%
“…The 2 species, H. intermedius and H . aimara, have identical 2n = 50 karyotypes, but 1 and 2 rDNA-bearing chromosome pairs, respectively [Blanco et al, 2011]. In contrast, in H. malabaricus (2n = 40/42), the number of NOR-bearing chromosomes ranges from 4 to 7 [Born and Bertollo, 2000;Cioffi et al, 2009].…”
Section: Interspecific and Intergeneric Variation In The Number And Lmentioning
confidence: 99%
“…Physical mapping studies of 5S and 18S rDNA have contributed to the cytotaxonomy and/or cytosystematics of different groups, e.g. Parodontidae (Bellafronte et al 2005), in Gymnotus (Silva et al 2011a), in Ancistrus (Mariotto et al 2011), in Pimelodus (Garcia and Moreira-Filho 2008), in Erythrinus (Blanco et al 2011), and in Loricariidae (Ziemniczak et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, reassociation kinetics based on C o t-1 DNA and the microdissection of chromosomes submitted to C-banding and the subsequent amplification of heterochromatic sequences using degenerate oligonucleotide-primed polymerase chain reaction (PCR) have been used successfully. [9][10][11][12][13][14] The Parodontidae is a Neotropical fish group that is divided into three genera: Parodon, Apareiodon, and Saccodon. 15 Cytogenetic studies reported a conserved diploid number of 54 chromosomes in Parodontidae with distinctive karyotype formulae and numerical/position variation of 18S and 5S rDNA sites.…”
mentioning
confidence: 99%